The Application of Cambridge Curriculum in English as Second Language Teaching Learning at Secondary School - Qomariyah, Dewi Nurul; Khasanah, Nur (Journal of Language Intelligence and Culture, 2023)
Pelita Hati Secondary School Jember implements Cambridge Curriculum as a holistic international curriculum which integrated learners from the primary until the high level. This school has been considered to be the only school that has a Cambridge curriculum’s licence in Jember. The research focus of this study are 1) Why does Pelita Hati Secondary School implement Cambridge curriculum?, 2) What is the concept of Cambridge curriculum applied at Pelita Hati?, 3) How is the implementation of Cambridge curriculum on English (as second language) teaching learning?. This study used qualitative approach with case study design. Data collecting techniques used in this study were observation, interview, and document review. To analyze the data, researcher use data condensations, data display, drawing and verifying conclusions from Miles and Huberman (2014). For data trustworthiness, researcher use source triangulation, technique triangulation. The findings showed that: 1) The Pelita Hati School implement Cambridge curriculum affected from the ANPS meeting conference in 2011. Because, in the prior time the school with a bilingual system since 2006 doesn’t has a certain curriculum to support their bilingual system. 2) The concepts of Cambridge curriculum in Pelita Hati in term of the components consist of the objective, the content, the process, and the evaluation components 3) Cambridge curriculum implementation in English subject include the planning, the content which consist of  learning activity (preliminary, core activity and closing activity),  global material, discussion method, projector and audio media and Evaluation include the placement test, classroom assessment, achievement test and diagnostic test.